Synthesis, characterizations and anti-corrosion screening of schiff base ligand with its mn(ii) complex / Nor Amiza Che’Zambeli - Che’Zambeli, Nor Amiza (Faculty of Applied Sciences, 2017)
Synthesis of Schiff base ligand N,N-Bis (4 chlorobenzaldehyde)- o - phenylenediamine (cbopd) derived from o-phenylenediamine with 4 chlorobenzaldehyde and its complex Manganese (II) N,N-Bis (4-chlorobenzal dehyde)- o -phenylenediamine dichloride dihydrate, [Mn(cbopd)].2H2O was successfully done via condensation reaction. The color of the ligand and complex formed were yellowish and brownish precipitates respectively. Both of the cbopd and [Mn(cbopd)].2H2O were characterized by using Fourier Transform Infrared (FT-IR) and Ultraviolet-Visible (UV-Vis) spectroscopy, elemental analyses, molar conductivity measurement and melting point determination. The elemental analyses revealed the actual value of the compounds obtained are quite different with theoretical value. Based on the FT-IR spectrum of ligand, several peaks appeared at 1607 cm-1, 3047 cm-1, 1492 cm-1, 830 cm-1 and 729 cm-1 have confirmed the presence of these major functional groups (C=N, =C-H, C=C, para-disubstituted and Ar-Cl) in the compound. Meanwhile, some of the peaks were shifted and a new peak were observed at 527 cm-1 in the FT-IR spectrum of [Mn(cbopd)].2H2O indicates formation of M-N bond. The melting point of cbopd and [Mn(cbopd)].2H2O were 176 °C and 230 °C respectively while molar conductance of [Mn(cbopd)].2H2O is 22.4 S cm-1. For the UV-Vis, there are absorption peaks at 212 nm and 238 nm attribute to π–π* and 300 nm were attribute to n–π* for the free ligand while in the complex, the bands for n–π* electronic transitions was shifted to 320 nm and a new peak were found at 370 nm indicates ligand to metal charge transfer (LMCT). Next, both cbopd and [Mn(cbopd)].2H2O were used as a corrosion inhibitor for the mild steel immersed in three different concentrations of hydrochloric acid for 48 hours at 50 °C. Generally, inhibition efficiency was found to be higher when the concentration of inhibitor increased and [Mn(cbopd)].2H2O was found to be a better corrosion inhibitor than free ligand, cbopd.